"Diversity" is the Highest Parameter Intensity of the use of Social Media in Adolescents - Heni Dwi Windarwati; Rachel Victoriana Raharjo; Muladefi Choiriyah (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Using social media can be reviewed through teens using social media. The intensity of the use of social media teenagers reaches one-sixth of the time in one day. This study aims to explore the use of social media in 10th-grade high school teenagers in Malang. This research uses descriptive. The measuring instrument used is the intensity questionnaire of social media use adopted from the Ardari research questionnaire. The number of samples in this study was 124 adolescents with a descriptive analysis method. The data analysis technique used is descriptive analysis. The intensity of the use of social media in 10th-grade teenagers in Malang is relatively high. The highest parameter of intensity use of social media with a high category is in the aspect of appreciation.